PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MTs BAHRIYATI QUR’ANIC BOARDING SCHOOL KOTA BENGKULU - Rival Riyuki; Salsabila; Utami Artiningsih; Bambang Irawan; Adi Saputra (STKIP Subang, 2025)
This study examines the learning problems of Islamic Religious Education (PAI) at MTs Bahriyati Qur’anic Boarding School in Bengkulu City. The research aims to identify the forms of obstacles encountered in the PAI learning process, analyze their influencing factors, and understand their implications for learning effectiveness. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation involving PAI teachers, boarding tutors, and students. The results show that PAI learning problems arise from three interconnected aspects: students’ varied initial abilities and learning fatigue, teachers’ limited use of innovative methods and digital media, and environmental challenges within the boarding system such as dense activity schedules and insufficient learning facilities. These findings indicate that improving PAI learning requires a holistic effort integrating pedagogical strengthening, better learning management, and enhanced technological support.